2021
DOI: 10.1088/1755-1315/657/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Health Risk Assessment of Antibiotics in Drinking Water of a City in Southern China

Abstract: In recent years, antibiotics have been widely used to treat some human and animal diseases, which due to their large production and usage. The antibiotic pollution in the environment has attracted more and more people’s attention. As a large country in the production and use of antibiotics, antibiotics has been detected in various environmental media in China, even in drinking water. However, drinking water is closely related to the health of residents. It is very necessary to understand the occurrence of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…These authors found values of the hazard quotient (HQ) ranged from 0.00000051 to 0.00215 due to the intake of untreated water from major Chinese watersheds and different drinking water sources, while in this work in children population the mean HQs were between 0.0003 and 0.002 for tetracycline and oxytetracycline, respectively. Liu et al (2021), who studied the presence of antibiotics in drinking water in a city in southern China, concluded that the main antibiotics in tap water in this area were tetracyclines and quinolones. The concentrations reported ranged from 0.227 to 0.498 µg/L and the risk assessment for the residents of this area when these waters are drunk indicated that it would not represent a risk to their health.…”
Section: The Results Of the Mean Hq For Flunixin And Antibiotics (Tet...mentioning
confidence: 99%
See 4 more Smart Citations
“…These authors found values of the hazard quotient (HQ) ranged from 0.00000051 to 0.00215 due to the intake of untreated water from major Chinese watersheds and different drinking water sources, while in this work in children population the mean HQs were between 0.0003 and 0.002 for tetracycline and oxytetracycline, respectively. Liu et al (2021), who studied the presence of antibiotics in drinking water in a city in southern China, concluded that the main antibiotics in tap water in this area were tetracyclines and quinolones. The concentrations reported ranged from 0.227 to 0.498 µg/L and the risk assessment for the residents of this area when these waters are drunk indicated that it would not represent a risk to their health.…”
Section: The Results Of the Mean Hq For Flunixin And Antibiotics (Tet...mentioning
confidence: 99%
“…(2017) found only one water sample with oxytetracycline, at a concentration of 0.6 μg/L, while Liu et al. (2021) detected antibiotics in the drinking water of a city in China, in concentrations from 0.227 to 0.498 μg/L, and with a high frequency (tetracyclines account for 25.8% to 64.3%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations